The Determinants and impacts of foreign direct investment on long-run growth in Jamaica - ROBERTS, Shernett (KDI School, 2015)
The aim of this study is to identify the determinants of foreign direct investment, and to further assess the impact of foreign direct investment on long-run growth in Jamaica over the period 1973 to 2010. Although Jamaica has witnessed a tremendous improvement in economic growth over the years, there is, however no conclusive evidence of this growth being linked to the increase in foreign direct investment inflows. The researcher however is not convinced that the strategies embarked upon by governments have attracted more foreign direct investment to the country than before. In analyzing the data using Ordinary Least Squares (OLS) model and Autoregressive Distributive Lag (ARDL) approach to cointegration the researcher found a mixed relationship between foreign direct investment and the macroeconomic variables analysed. Return on capital and exchange rate was found to have a negative but statistically significant influence on foreign direct investment. Gross fixed capital formation was also found to have a negative but statistical insignificant influence on foreign direct investment. Trade openness, inflation rate, government size and political party exhibited positive but insignificant influence on foreign direct investment. Political party was used as a dummy variable to capture the political climate under which economic actions are taken. The Autoregressive Distributive Lag approach to cointegration analysis revealed the presence of a long-run equilibrium relationship between foreign direct investment and economic growth, nonetheless foreign direct investment does not have any significant effect on the growth as well as the development of Jamaica’s economy during the period. The researcher therefore recommend the government to ensure stable macroeconomic policies and increase its expenditure in the area of infrastructural development as ways to accelerate the growth of Jamaican economy which will reduce the excessive dependence of Jamaica on foreign direct investment.
Thesis(Master) --KDI School:Master of Development Policy,2015